Femme nue, femme noire of Calixte Beyala front "Femme noire" of Leopold Sedar Senghor (Castilla. Estudios de Literatura, 2013)
The aim of this study is to demostrate through certain semiotical-discursive elements like intertextuality, dialogism, polifony, transtextuality, paratextuality, etc…, that every text is an intertext. That is the case of Calixte Beyala’s novel Femme nue, femme noire which has been inspirated by the Leopold Sédar Senghor’s poem Femme noire. Although both authors don’t belong to the same generation, and have different perspectives on the matter, they demostrate the same attachment to Africa in general and to the african woman in particular. Both defend, consciently or not the well-known ideological and literary african mouvement named Negritud.